Applying Transformational Generative Grammar on Ellipsis Analysis of The Short Story Hills Like White Elephants by Ernest Hemingway - Fera Andri Yani (English Department, Faculty of Humanities, Andalas University, 2015)
This research deals with the base structures and the transfomational processes that are used to find out the types of ellipsis occur in the ellipted sentences in the short story entitled Hills Like White Elephants by Ernest Hemingway. In collecting the data, the method used is observational method, while in analyzing the data is ditributional method. Both are referring to the methods proposed by Sudaryanto (1993). The main theory used to analyze the data are ellipsis as developed by Quirk and Greenbaum (1990) and Transformational Generative Grammar by Huddleston (1976). The data analyzed are fifteen sentences that contain ellipsis. The result shows that there are six types of transformational process occur in the data; conjunction shift, deletion, particle shift, not placement, do-support and affix hopping. Those processes are used to convert the deep structure into the surface structure. In addition, ellipsis frequently occurs in the elements such as subject, auxiliary and predicate.Keywords: ellipsis, base strcuture, transformational process